Spatiotemporal Distribution of nirS-Type Denitrifiers in Cascade Reservoir Sediments of the Qinghai Plateau - Yi Wu; Xufeng Mao; Hongyan Yu; Hongyan Li; Feng Xiao; Yuhua Mo; Haichuan Ji; Yuanjie Ma (Diversity)
Compared to single damming, the impact of cascade damming on nitrogen-related microorganisms in river ecosystems exhibits greater complexity. However, there is still a lack of research on the response of denitrifiers to the construction of cascade reservoirs. A study was conducted on 10 cascade reservoirs in the upper reaches of the Yellow River to investigate the impact of cascade reservoir construction on nirS-type denitrifying bacteria in sediments. Sediment samples were collected in May (dry season) and August (wet season) of 2023. The spatiotemporal characteristics of the nirS-type denitrifying bacterial community and gene abundance were analyzed using Illumina high-throughput sequencing and real-time fluorescence quantification PCR (qPCR). Redundancy analysis (RDA) and variation partitioning (VP) were utilized to assess the impact of environmental factors on these communities. The results showed the following: (1) Proteobacteria was the predominant phylum of nirS-type denitrifying bacteria in cascade reservoir sediments. At the genus level, unclassified Proteobacteria (69.51–95.64%) showed the highest relative abundance, followed by Paracoccus, Rhodanobacter, and Pseudomonas, indicating that unclassified Proteobacteria may dominate denitrification in these reservoir sediments. (2) The α and β diversity indices of nirS-type denitrifying bacteria were higher in the dry season than in the wet season, and also higher in young reservoirs compared to old reservoirs (p < 0.05). (3) Temporally, the abundance of the nirS gene was significantly higher in the wet season (12.71 × 107 copies/g dry sediment) compared to the dry season (66.35 × 105 copies/g dry sediment). Spatially, the abundance of the nirS gene was higher in the central region, while relatively lower at both ends. (4) RDA and VP analysis indicated that the community structure and abundance of nirS-type denitrifying bacteria were significantly influenced by the total nitrogen in sediments (19.31%) and water temperature (14.13%). Spearman correlation analysis showed that organic carbon significantly affected the diversity of nirS-type denitrifying bacteria (p < 0.05). The results contribute to a better understanding of the nitrogen-related microbial community in cascade reservoir sediments of the Yellow River, providing a scientific basis for reservoir management.